Scapholunate ligament injury adversely alters in vivo wrist joint mechanics: An MRI‐based modeling study. Issue 9 (10th April 2013) - Johnson, Joshua E.; Lee, Phil; McIff, Terence E.; Toby, E. Bruce; Fischer, Kenneth J.
Abstract We investigated the effects of scapholunate ligament injury on in vivo radiocarpal joint mechanics using image‐based surface contact modeling. Magnetic resonance images of 10 injured and contralateral normal wrists were acquired at high resolution (hand relaxed) and during functional grasp. Three‐dimensional surface models of the radioscaphoid and radiolunate articulations were constructed from the relaxed images, and image registration between the relaxed and grasp images provided kinematics. The displacement driven models were implemented in contact modeling software. Contact parameters were determined from interpenetration of interacting bodies and a linear contact rule. Peak and mean contact pressures, contact forces and contact areas were compared between the normal and injured wrists. Also measured were effective (direct) contact areas and intercentroid distances from the grasp images. Means of the model contact areas were within 10 mm2 of the direct contact areas for both articulations. With injury, all contact parameters significantly increased in the radioscaphoid articulation, while only peak contact pressure and contact force significantly increased in the radiolunate articulation. Intercentroid distances also increased significantly with injury. This study provides novel in vivo contact mechanics data from scapholunate ligament injury and confirms detrimental alterations as a result of injury. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1455–1460, 2013